Influence of color steel buildings on urban land surface temperature: a case study in Urumqi, Xinjiang, China - Li, Yuqing; Yang, Shuwen; Luo, Yawen; Zhang, Zhengrong; He, Pengcheng (Frontiers in Environmental Science, 2024)
Highly clustered color steel buildings (CSB) have become new impervious surfaces and heat island areas in cities due to their materials, especially in the Northwest. However, the extent of the influence of CSB on land surface temperature (LST) and how they are quantitatively related to each other have not been explored. Therefore, this paper takes Urumqi city, which is densely populated with CSB and has a unique topography, as an example. We obtained LST data and CSB data based on Landsat and Google Earth images, and quantitatively analyzed the warming effect of the CSB on the urban LST and the characteristics of regional variability. The results of the study showed that from 2005 to 2020, the scale of CSB in Urumqi City has been expanding, with highdensity aggregation shifting from urban areas to the suburbs. The urban area of Urumqi city shows a "cool island effect", with higher temperatures in CSB. The high-density distribution of CSB roughly coincides with the high temperature areas of the city. The density of CSB is highly positively correlated with LST, with the correlation coefficient reaching 0.973 in 2010. For every 0.2 increase in cluster density, the corresponding temperature can rise by 0.4°C. At the same density of aggregation, the average temperature of urban CSB is lower than that in the suburbs. The contribution index of suburban CSB to LST reaches 0.512, significantly higher than the surrounding other buildings, marked it one of the main contributors to the thermal environment in the suburbs. The research results can provide a reference and data support for the sustainable development and planning of cities.